Development of an appropriate medical certificate of employment for administrative purposes - P, Subsookumnuay; N, Chaiear; P, Krisorn (Biomedical Sciences and Clinical Medicine, 2021)
Objectives The study aimed to develop a ‘fit to work’ certificate written in a format appropriate for Thai culture and law and to canvas the opinions of stakeholders regarding a ‘fit to work’ certificate. Methods The Modified Delphi technique was used to canvas the opinions of experts in 13 clinical disciplines and medical law specialties. The study was divided into two phases: Phase 1 was a questionnaire survey regarding ‘fit to work’ certificates around the world and the opinions of experts in the medical field about aspects of ‘fit to work’ certificates. Phase 2 was a study of the opinions of stakeholders working in the medical profession in different capacities. Results Study results indicated that a medical certificate should include 14 elements. In round 1, the cohort of experts agreed on all existing components and recommended 5 additional elements. In round 2, the experts agreed (median 4 to 5), while in round 3, the experts agreed on all suggested components except component 19. In phase 2, each component was judged suitable for use in the Thai context. Conclusions None of the components in the proposed certificate contravene Thai law, especially regarding the confidentiality of some information, and the certificate can be used to collect data regarding potential workplace-related health problems, thereby enabling employees who are fit to work and to return to their job. Training physicians on how to complete a ‘fit to work’ certificate may be necessary.